Technologies and Properties of Modern Utility Materials XXII - Mendala, Jacek; Gradoń, Paweł (Diffusion and defect data. Solid state phenomena ;, 2015)
Collection of selected, peer reviewed papers from the XXII Conference on Technologies and Properties of Modern Utility Materials, (TPMUM 2014), May 16, 2014, Katowice, Poland. The 42 papers are grouped as follows: I: Materials Analysis; II: Processing Technologies; III: Surface Engineering; IV: Materials and Environment.